Penatalaksanaan ankyloglossia pada anak - Supit, Ivana; Widodo, Dini Widiarni (PERHATI-KL, 2025)
Background: Ankyloglossia, or tongue-tie, is a congenital oral anomaly characterized by an abnormally short, thick, or tight lingual frenulum that restricts tongue mobility. While mild cases may be asymptomatic, moderate to severe cases can impair essential functions such as breastfeeding, swallowing, mastication, speech articulation, and oral hygiene. In children, untreated ankyloglossia may also affect psychosocial development, including self-esteem and interpersonal communication. Purpose: To provide a comprehensive overview of ankyloglossia, emphasizing its anatomical and clinical aspects, classification systems, diagnostic tools, and current treatment options. Literature review: A narrative review was conducted using relevant literature from peer-reviewed journals and academic textbooks. The review covers various classification systems such as the Coryllos and Kotlow classifications, which assist clinicians in assessing severity, and determining management. Clinical manifestations vary with age and may include breastfeeding difficulties in infants, speech disturbances in children, and social or functional challenges in adults. Diagnostic approaches rely on clinical examination and standardized assessment tools like the Hazelbaker Assessment Tool for Lingual Frenulum Function (HATLFF). Management approaches include conservative methods or surgical intervention, with options such as frenotomy, frenectomy, or frenuloplasty, depending on the patient’s age and symptom severity. Conclusion: Ankyloglossia can significantly affect oral function and quality of life. Early recognition and appropriate intervention are essential for preventing long-term complications. Standardized diagnostic criteria and evidence-based treatment guidelines are needed to optimize care and ensure consistent clinical outcomes.